\[\boxed{\text{1200\ (1200).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[n^{3} - n = n \cdot \left( n^{2} - 1 \right) =\]
\[= n(n - 1)(n + 1) - получили\ \]
\[произведение\ из\ трех\ \]
\[последовательных\ чисел,\ тогда\ \]
\[одно\ точно\ четное,\ а\ другое\]
\[делится\ на\ 3,\ тогда\ все\ \]
\[произведение\ делится\ на\ 6.\ \]
\[\boxed{\text{1200.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ A\ ( - 4;0);\ \ B\ (0;2):\]
\[y = kx + b\]
\[0 = - 4k + b\]
\[4k = b\]
\[2 = 0 + b \Longrightarrow \ \ b = 2\]
\[Тогда:\ \ \]
\[4k = 2 \Longrightarrow \ \ k = 0,5\]
\[2)\ C\ (0;\ - 3);\ \ D\ (5;0):\]
\[y = kx + b\]
\[- 3 = 0 + b \Longrightarrow \ \ b = - 3\]
\[0 = 5k - 3\ \ \]
\[5k = 3 \Longrightarrow \ \ k = \frac{3}{5} = 0,6\]